Nanocellulose and its derived composite electrodes toward supercapacitors: Fabrication, properties, and challenges - Junlei Xiao; Huiling Li; Hua Zhang; Shuijian He; Qian Zhang; Kunming Liu; Shaohua Jiang; Gaigai Duan; Kai Zhang (Journal of Bioresources and Bioproducts, 2022)
With the increasing demand for sustainable energy storage systems, the development of various advanced materials from a renewable source is imminent. Owing to the advantages of high specific surface area, unique nanostructure, modifiability, and excellent mechanical strength, nanocellulose integrated with other conductive materials, such as nanocarbons, conducting polymers, and metal oxides, has been emerged as promising candidate materials for green and renewable energy storage devices. Besides, nanocellulose-derived carbon materials with good electrical conductivity and tunable microstructures can be fabricated via simple carbonization, which has been widely used as supercapacitor electrode materials. Herein, we present a comprehensive review that focuses on the development of nanocellulose materials for sustainable energy storage, particularly on supercapacitors. The fabrication strategies of nanocellulose-derived hybrid materials are first presented and summarized, followed by highlighting the use of natural nanocellulose for constructing composite electrode materials including two-dimension film electrodes, and three-dimension aerogel electrodes for supercapacitors. In addition, the possible limitations and potentials of nanocellulose in supercapacitors are outlooked.